Right to quality education in the exercise of teaching learning in Brazil (Research, Society and Development, 2022)
Teaching learning to result in good quality teaching requires responsibility, commitment, seriousness and agreements that are fulfilled. In this way, the general objective is to analyze the right to quality education in the exercise of teaching and learning in Brazil and has the following specific objectives: To show quality education based on the Brazilian Federal Constitution; present the Education Development Plan (PDE); highlight the National Education Plan (PNE). As for the Methodology, it is qualitative bibliographical research, being a systematic review. The search for data was carried out on academic Google, Scielo (through books, articles and magazines already published), as well as on the Laws that support the right to education. The right to education stems from the recognition that systematic knowledge is more than an important cultural heritage. As part of the cultural heritage, the citizen becomes capable of taking hold of cognitive and training standards through which he has greater possibilities of participating in the destinies of his society and collaborating in its transformation. Having mastery of systematic knowledge is also a “sine qua non” level in order to be able to broaden the field and horizon of this and new knowledge. The study tends to visualize the important role of government Projects and Plans, such as PNE, PDE, FUNDEB and others, in relation to the enhancement of education, through bodies responsible for its smooth progress and development, so that there is a satisfactory and satisfactory result. positive.